Pengaruh Female Director, Institutional Ownership, Dan Profitability Terhadap Intellectual Capital Disclosure - Andre Lorensa, Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study has purpose to determine the influence of female directors, institutional ownership, and profitability on intellectual capital disclosure. This study uses manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. This study used a purposive method in sampling and 39 companies was obtained. This study uses a fixed effect panel data model after conducting a chow test and a hausmann test. This study uses E-views 10 in data processing. The results of this study is that female directors have a positive influence on intellectual capital disclosure, while institutional ownership and profitability do not have an influence on intellectual capital disclosure.